Perbedaan Kandungan Vitamin C Dan Serat Kasar Pada Jus Jeruk Siam Banjar (Citrus Nobilis Var. Microcarpa) Yang Diolah Menggunakan Berbagai Alat Pengolahan Jus - Nany Suryani; Rissa Saputri; Hanan Hanan; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Juice is the alternative material of healing and to fulfill nutrient. Orange juices is most often available where ever, either in café, restaurant or hotel. Orange juice is also easy to make. Citrus fruits are famous rich in vitamin C and fiber. Vitamin C and fiber are the nutrients that have many roles in maintaining a healthy body. There are 3 way to make a juice, such as Squeezing, use Blenders and Juicers. The third equipment has a different way of working in which ways of working of each juice processing devices have the potential to result in reduced content of vitamin C and fiber in the juice produced. This study uses orange Siam Banjar. The research goal is to determine the content of vitamin C and crude fiber in each juice is processed using a variety of juice processing equipment, as well as to determine whether there is a difference in vitamin C and crude fiber in the juice produced in order to process the juice with vitamin C and knowing enough juice processing equipment that produces juice with vitamin C and fiber content of most rough. The content of vitamin C was analyzed using Iodimetri while crude fiber method using a gravimetric method. Based on the results of the ANOVA test vitamin C showed p <α is the difference between the vitamin C content of the juices. Juice has the highest content of vitamin C found in processed juice using Juicer. The juice has 11,264 of vitamin C. ANOVA test results showed crude fiber p <α it is mean the difference between the crude fiber content of the juices. Juice which has the highest crude fiber content is juice processed using Blender. The juice has 6,320% of crude fiber.